Fast growth of monocrystalline thin films of 2D layered hybrid perovskite. Issue 19 (29th March 2017) - Lédée, Ferdinand; Trippé-Allard, Gaëlle; Diab, Hiba; Audebert, Pierre; Garrot, Damien; Lauret, Jean-Sébastien; Deleporte, Emmanuelle
Abstract : Hybrid organic–inorganic perovskites are on the way to deeply transforming the photovoltaic domain. Abstract : Hybrid organic–inorganic perovskites are on the way to deeply transforming the photovoltaic domain. Likewise, it recently appeared that this class of material has a lot of potential for other optoelectronic applications. One key aspect is to be able to synthesize monocrystalline thin films with large surface areas. Here, we report on the development of a new synthesis method for 2D hybrid organic–inorganic perovskite called "Anti-solvent Vapor-assisted Capping Crystallization". This method allows us to grow monocrystalline thin films with a high aspect ratio in less than 30 minutes.